Total phenolic content, antioxidant, and antimicrobial activities of ripe and unripe Ghanaian habanero pepper (Capsicum chinense) - Aaron Dzigbor; David Neglo; Clement O. Tettey; Frank Nsaful; Francisca Adzaho; Esther Mawusey Botchway (Food Chemistry Advances)
This study compared the total phenolic content, antioxidant activity, and antimicrobial activity of ripe and unripe Ghanaian habanero pepper (Capsicum chinense) against some selected foodborne pathogens. The total phenolic content (TPC) of the pepper extracts was determined using the Folin-Ciocalteu method, while the radical scavenging potential of the pepper extracts was assessed using the DPPH and ABTS assays. Determination of minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), combinatory effects with standard antimicrobial agents, and inhibition of biofilm formation were used to assess the antimicrobial activity of the pepper extracts. The results showed that the ripe pepper extract outperformed the unripe pepper extract in terms of TPC and radical scavenging potential. The TPC values of 1004.52 µgGAE/g and 1362.79 µgGAE/g were obtained for unripe pepper and ripe pepper extract, respectively. DPPH and ABTS free radical scavenging potential were 28.80 % and 91.32 % for unripe extracts and 34.27 % and 92.96 % for ripe pepper extract. In addition, varying degrees of MIC and MBC were obtained for both the unripe and ripe pepper extracts against test organisms. Combinatory effects with antimicrobial agents and antibiofilm formation activity varied for both pepper extracts. In conclusion, the use of pepper in food preparation could help reduce the menace of foodborne diseases.